DEVELOPMENT OF CRAFT FIELDS OF THE POPULATION OF THE MOUNTAIN PEOPLE (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article describes the achievements and history of the people of Surkhan oasis in the fields of handicrafts: blacksmithing, engraving, coppersmithing, carving, and jewelry.